DEVELOPMENT OF ANDROID-BASED HIGH JUMP POLE DEVICE AS A LEARNING MEDIA FOR ATHLETICS COURSES - Widowati, Atri; Diana, Fitri; Decheline, Grafitte; Hasibuan, Mhd Usni Zamzami; Murniati, Sri (STKIP Singkawang, 2024)
In the digital era, the world of sports must not be left behind to be able to follow a more sophisticated era. There needs to be a new breakthrough for the development of sports equipment that was originally manual into digital sports equipment that has sophisticated technology. With the development of more sophisticated sports equipment, it can easily achieve success in the field of sports. The high jump number in the athletics branch of sport is the most popular branch of sport. However, currently the high jump equipment used is still manual so it is less effective and efficient considering that the high jump competition requires time effectiveness between athletes. The development of high jump equipment aims to facilitate and make the time required more efficient. The high jump equipment was developed using a node mcu microprocessor. And a microcontroller to adjust the height of the high jump bar. The equipment that has been developed was then tested on 7 high jump athletes. Based on the trial, the results obtained were the percentage of tool effectiveness of 42%, tool safety of only 32%, tool efficiency and economy of 42%, ease of use of 54%, the smallest percentage was obtained by ease of tool placement of only 29%, while the highest percentage was in Long-Term Usefulness (PJJ) of 71%. So that the development of the tool is in the Good category with a percentage of 71%.